The Helicase PIF1 Facilitates Resection over Sequences Prone to Forming G4 Structures - Sonia Jimeno; Rosa Camarillo; Fernando Mejías-Navarro; Maria Jesús Fernández-Ávila; Isabel Soria-Bretones; Rosario Prados-Carvajal; Pablo Huertas (Cell Reports, 2018)
Summary: DNA breaks are complex lesions that can be repaired either by non-homologous end joining (NHEJ) or by homologous recombination (HR). The decision between these two routes of DNA repair is a key point of the DNA damage response (DDR) that is controlled by DNA resection. The core machinery catalyzing the resection process is well established. However, little is known about the additional requirements of DNA resection over DNA structures with high complexity. Here, we found evidence that the human helicase PIF1 has a role in DNA resection, specifically for defined DNA regions, such as those prone to form G-quadruplexes. Indeed, PIF1 is recruited to the site of DNA damage and physically interacts with proteins involved in DNA resection, and its depletion causes DNA damage sensitivity and a reduction of HR efficiency. Moreover, G4 stabilization by itself hampers DNA resection, a phenomenon suppressed by PIF1 overexpression. : DNA resection machinery is well established in eukaryotes. However, little is known of the accessory factors required to resect over atypical DNA structures. In this paper, Jimeno et al. show that the helicase PIF1 facilitates resection, particularly at complex sequences that tend to form G-quadruplexes. Keywords: DNA end resection, PIF1, DNA recombination, G-quadruplex, DSB repair, DNA repair, BRCA1